Analysis on Influence of Residents’ Response Probability Distribution on Load Aggregation Effect - Zhang, Weichun; Hu, Qinran; Yu, Xiaorong (Frontiers in Energy Research, 2022)
Residential loads are essential resources, and they can participate in grid scheduling through aggregation, with great potential. However, inherent uncertainties challenge the realization of accurate load aggregation (LA), leading to the failure to fully play a role in grid operation. In this context, this paper analyzes the influence of the probability of residents participating in LA on the actual aggregation effect. Firstly, the LA problem is modeled, and the optimization objective is equivalently transformed from minimizing the mismatch between the actual load regulation and the target to minimizing the sum of variances of the overall response probabilities. Response probabilities of residents are then simulated based on the β distribution model, and various typical distributions can be generated by modifying only two hyperparameters. In order to evaluate the actual aggregation effect, a multi-armed bandit model that can be used for LA is adopted, and an evaluation framework is designed. The simulation results show that for different probability distributions, the smaller the sum of variances of all residents’ response probabilities are, the more accurate aggregation can be achieved.